2013
DOI: 10.1039/c2ra21912c
|View full text |Cite
|
Sign up to set email alerts
|

A growth kinetic study of ultrafine monodispersed silver nanoparticles

Abstract: In this article we report the growth kinetics of ultrafine monodispersed silver nanoparticles prepared via thermal reduction of silver nitrate with oleylamine. Effect of nucleation and growth temperature and time on the quality and quantity of silver nanoparticles was monitored in terms of product yield, crystal phase, morphology, aggregation, particle size and size distribution. To understand the effect of kinetic parameters, purified silver nanoparticles were characterized by UV-visible, FTIR and photon corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Based on our previous work, 28,29 SNPs were prepared by two step chemical reduction method. In the first step, oleylamine capped hydrophobic SNPs are produced by reducing AgNO 3 with oleylamine.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous work, 28,29 SNPs were prepared by two step chemical reduction method. In the first step, oleylamine capped hydrophobic SNPs are produced by reducing AgNO 3 with oleylamine.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…We have observed that the size of the NPs and their aggregation is strongly influenced by various synthesis parameters like concentration of AgNO 3 and oleylamine, nucleation temperature, nucleation time, growth temperature, and growth time. 29 Effect of each of these parameters on the particle quantity (yield) and quality (size, size distribution, and shape) were investigated in detail and reported elsewhere. 29 In the present study, we have prepared two samples of SNPs with average hydrodynamic size of 83 and 59 nm, respectively.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…This observation is consistent with the presence of single plasmon peak in UV-Visible spectroscopy. Size distribution histogram was fitted with lognormal size distribution function [10]. The hydrodynamic size corresponding to the long axis of GNRs is ≈ 60 nm while the short axis is ranging between 2-20 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Values close to zero indicate a monodispersion (particles with equivalent sizes), whereas high values indicate a tendency towards heterogeneous suspensions. The authors agree that values below 0.2 characterize a suspension trend to monodispersion (CHANDINI, et al, 2013). This parameter is quantified by the result of the hydrodynamic diameter size distribution of the agglomerates of AgNPs in the solution conducted by DLS.…”
Section: Synthesis and Characterizationmentioning
confidence: 87%